The Strategic Role of Theological School in Efforts to Formation of Excellent Indonesian Human Resources: Peran Strategis Sekolah Teologi dalam Upaya Pembentukan Sumber Daya Manusia Indonesia yang Unggul - Kalis Stevanus (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2022)
At this time, the era of disruption is characterized by technological developments and inventions that are all modern, there is a tendency for education in building society to forget and be dissolved by the current of secularization so that humans increasingly prioritize science and tend to ignore moral principles. School of Theology exists as a formal forum for the formation of superior human resources. The method used is a qualitative method with a library approach. It is concluded that the School of Theology has a strategic role to continue to strive to improve the quality of education in order to produce superior human resources to be sent to serve God's people, as follows: first is the need to prioritize the competence of expertise (professionality) and noble character (spirituality) of educators; second is adaptive to advances in technology and information so that the learning process is effective; the third is a balanced curriculum in both academic and practical aspects. These three things will improve intellectual abilities, skills and shape the character of students.